Phosphatidylcholine (lecithin) stimulating effect on pathogenic properties of pneumococcus - A. S. Kvetnaya; L. I. Zhelezova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The authors have studied the effect of phosphatidylcholine (lecithin) - a derivative of choline - on the biological properties of streptococus pneumonia. The concentration of lecithin 0.01 g/l in a simple nutrient broth has a stimulating effect on proliferation, on in vitro stabilization of the population, and on pathogenic properties of the pneumococcus. Four - five times passaging of the strains on this medium (as opposed to the commonly used 20 % serum broth) retained the species and the typical properties of pneumococcus, but led to increased capsule formation, increased virulence and expressed β-hemolytic activity. These results suggest that phosphatidylcholine (lecithin), as the main supplier of pneumococcus growth stimulant - choline, has an expressing impact on the capsule formation - the main pathogenic factor, and on the substance of P-teichoic acid in the cell wall of pneumococcus that specifically interacts with the C-reactive protein.